THE IMAGE OF EDUCATORS IN CHARLES DICKENS’ DAVID COPPERFIELD - Safarova Zilola Tolibovna; Amonova Gulnoza (Bright Mind Publishing, 2025)
This article studies the role of educator characters in Charles Dicken’ “David Copperfield”. As a Bildungsroman novel that depicts personal-development, David Copperfield explores protagonist’s life from troubled childhood to responsible adulthood. The protagonist becomes mature with a profound influence of both formal educators and life mentors. By analyzing characters of Mr Creakle, Dr. Strong, Mr. Micawber, James Steerforth, Aunt Betsey and Agnes Wickfield, we will learn how Dickens creates various models of education and mentorship in order to reflect the values of the Victorian era critique an institution’s shortfalls, as well as depict the complex process of person’s moral and intellectual development.
Keywords: Educator, mentor. modern education, Charles Dickens, moral education.